К фауне саркофагид (Diptera, Sarcophagidae) СССР. II. Подсемейства Sarcophaginae (триба Agriini), Mascronichiinae и Miltogrammatinae - Вервес, Ю.Г. (Вестник зоологии, 1975)
The given information is the second part of the previously published work. It deals with data on distribution of 23 species belonging to 18 genera of three subfamilies.